Supply Chain Management Effects on the Tax Information as the Basic Supporting Revenues in Iraq for the period from 2014-2018 - Hayder Kareem Salim; Hayder Oudah Kadhim; Wissam Abdulkadhum Abdulridha (International Journal of Supply Chain Management, 2019)
Many organisations are beginning to consider the merits of moving to a tax-efficient supply chain and procurement model, both through information management and also centralizing purchasing and supply operations in a tax-efficient location. Tax-efficient sourcing integrates supply chain and procurement-operating model design with tax planning to deliver significant cost reductions and profit increases through centrally controlling procurement operations. This research is intended to examine information management and technologies in tax support as basic source for developing the revenues, also its effect on total revenues in Iraq from 2014 till 2018. The analysis of tax support literature suggest that we have various kinds of tax support, classifications and effects of tax support, social and economic significance and response to tax support which needs analysis. The empirical analysis has been done with the data of total public revenues of Iraq starting from 2014 to 2018. For analysis techniques the descriptive statistics are employed. From previous studies it has been discovered that significance of total revenues are associated with basic tax support which is the ground for National budget. Likewise, rate of growth and the tax revenues for the time before 2014, in that we can see change in Iraqi regime, also its openness towards world. It draws it from an economy of socialist nature to an economy based on market based on the supply chain. Similarly the effect of supply chain on tax support on direct tax income and also on withholding tax, also the effect of information management tax Revenues on Total Country Revenues.